Kolej Kediaman Lestari: Keselesaan Bilik Penghuni Kolej Kediaman Tun Fatimah, Universiti Tun Hussein Onn Malaysia: Sustainable Residential College: Room Comfort at Tun Fatimah Residential College, Universiti Tun Hussein Onn Malaysia - Buyung, Mohd Reduan; Shafii, Haryati (GEOGRAFI, 2016)
This study is an initial study for the development of the concept of sustainable residential college in Malaysia. This article examines the comfort level staying in Tun Fatimah residential college, University Tun Hussein Onn Malaysia. The methodology used was through the questionnaires to 40 respondents. The questionnaire are divided into two parts, which are part A related to respondents' demographic that contains three items and Part B relates to the convenience of residential college accommodation which contains 11 question items. Besides, section B also contains two sub-topics, the comfort of physical space and residents comfort for indoor facilities. The obtained data were analysed using percentages to determine the residents’ comfort level that refers to each question items. The results from all eleven questions on residents’ comfort for the rooms indicate that the resident rooms was at comfortable level and this indicates that the college provides the good accommodation to meet the current needs for the residents. A comfortable accommodation is important so that the residents able to concentrate while doing revision and get enough rest, thus could improve the quality of life while stay in the residential colleges.